Political oratory and cartooning : an ethnography of democratic processes in madagascar - Jackson, Jennifer (Jennifer L.) (Chichester, West Sussex, UK ; Malden, MA : Wiley - Blackwell, 2013)
Jackson traces the lively skirmishes between Madagascar's political cartoonists and politicians whose cartooning and public oratory reveal an ever-shifting barometer of democracy in the island nation. It is the first anthropological study of the role of language and rhetoric in reshaping democracy and maps the dynamic relationship between formalized oratory, satire, and political change in Madagascar.
1. Introduction: "Look out! The sleeping locusts awake" -- 2. A history of language and politics in Madagascar -- 3. The structural and social organization of kabary politika -- 4. The structural and social organization of kisarisary politika (political cartooning) -- 5. Building publics through interanimating and shifting registers -- 6. "Stop acting like a slave" : the ideological and aesthetic dimensions of syntax and register in political kabary and political cartooning -- 7. "That's what you think" : arguing representations of truth in language -- 8. Conclusion: The constraints and possibilities of democracy.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: 1992-2010; Presidents -- Madagascar -- Election; Political campaigns -- Madagascar; Political consultants -- Madagascar; POLITICAL SCIENCE -- Political Process -- Elections; POLITICAL SCIENCE -- Political Process -- General; Political campaigns; Political consultants; Politics and government; Presidents -- Election; Madagascar -- Politics and government -- 1992-2010.; Madagascar; Electronic books